Community-based physical activity programs for brazilian adults evaluated using the re-aim framework: a systematic review - Goveia, Jean Carlos de; Carmo, Gonçalo Cassins Moreira do; Vargas, Thaiane Moleta; Pedroso, Bruno; Vargas, Leandro Martinez (Journal of Physical Education (Maringá), 2025)
This systematic review aimed to describe the methodological characteristics of studies that applied the RE-AIM framework to evaluate community-based physical activity programs in Brazilian adults. The search was conducted on August 8, 2024, in six databases (Web of Science, PubMed, Scopus, Embase, LILACS, and SciELO). Original studies that used the RE-AIM framework to evaluate community-based physical activity programs involving adults without specific health conditions were included. A total of 1,563 articles were identified, of which six were included in the synthesis. These studies were predominantly conducted in the southern region of Brazil, with interventions also implemented in the southeastern and northeastern regions, mainly involving female samples with an average age between 40 and 70 years. The findings highlighted challenges in reaching and sustaining interventions, particularly among vulnerable populations. Conversely, programs integrated into the healthcare system and supported by ongoing institutional backing demonstrated higher adherence rates. In summary, future research is crucial to deepen the understanding of factors influencing the sustainability of physical activity interventions and the relationship between public policies and community-based programs. The adoption of self-monitoring strategies, continuous support, and institutional engagement stand out as key elements to ensure the maintenance of healthy behaviors and the long-term effectiveness of interventions.